Google apps hacks - Lenssen, Philipp; Safari eBooks (Sebastopol, Calif. : O'Reilly Media, 2008)
Can Google applications really become an alternative to the venerable Microsoft Office suite? Conventional wisdom may say no, but practical wisdom says otherwise. Google apps hacks gets you in on the action with several ingenious ways to push Google's web, mobile, and desktop apps to the limit. The hacks and workarounds in this book help you get more than the obvious out of a whole host of Google's web-based applications for word processing, spreadsheets, PowerPoint-style presentations, email, calendar, and more by giving you ways to exploit the suite's unique network functionality--From publisher description.
Meet the Google docs family -- The Google docs family : Google documents -- The Google docs family : Google spreadsheets -- The Google docs family : Google presentations -- Become a Gmail power user -- Customize your Google home page -- Manage your events with Google calendar -- Keep up on news with Google reader -- Manage your photos and videos with Picasa and Youtube -- Create your own home page, blog, or group -- Dive into Google maps, Google earth, and Sketchup 3D -- Google analytics and beyond : market your site, track visitors.
Title from title screen.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Google; Electronic books